Automatic Waste Management System with RFID and Ultrasonic Sensors - Amritkar, MV (International Journal of Computer Sciences and Engineering, 2025)
Radio Frequency Identification (RFID) is a technology that can be used to automate waste management by providing details about the waste and sending massage to the system about the collected bins. In this paper, we are proposing a smart bin application based on RFID tags which contain information of each waste item. The wastes are tracked by smart bins using a RFID-based system without requiring the support of an external information system. Because of this system, the user is helped in the application of selective sorting and smart waste management system will come to know the status of the bin using ultrasonic sensors. Automatic Waste Management System helps to keep track of empty bins and also will give information about the filled bins to collective vehicles which will help them to collect filled bins with proper management automatically reduce the human efforts. This system will surely keep society hygiene and reduce air pollution spread by waste.